2013 28th Annual ACM/IEEE Symposium on Logic in Computer Science 2013
DOI: 10.1109/lics.2013.56
|View full text |Cite
|
Sign up to set email alerts
|

Rabin-Mostowski Index Problem: A Step beyond Deterministic Automata

Abstract: Abstract-For a given regular language of infinite trees, one can ask about the minimal number of priorities needed to recognise this language with a non-deterministic or alternating parity automaton. These questions are known as, respectively, the non-deterministic and the alternating Rabin-Mostowski index problems. Whether they can be answered effectively is a long-standing open problem, solved so far only for languages recognisable by deterministic automata (the alternating variant trivialises).We investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 20 publications
(23 reference statements)
0
16
0
Order By: Relevance
“…Despite structural simplicity, they have enough expressive power to inhabit all levels of the non-deterministic index hierarchy and the alternating index hierarchy. In [FMS13] it was shown that these two hierarchies are decidable when the input language is recognized by a game automata.…”
Section: Lemma 2 If Wclass(mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite structural simplicity, they have enough expressive power to inhabit all levels of the non-deterministic index hierarchy and the alternating index hierarchy. In [FMS13] it was shown that these two hierarchies are decidable when the input language is recognized by a game automata.…”
Section: Lemma 2 If Wclass(mentioning
confidence: 99%
“…In [FMS13], it was shown that for the class of game automata (the closure of the class of deterministic automata under complementation and substitution) the non-deterministic and alternating index problems are solvable. The deterministic index problem being already solved by [NW98], the only case left is the weak index, known to coincide with the quantifier alternation depth for the weak monadic second order logic [Mos91b].…”
Section: Introductionmentioning
confidence: 99%
“…Deciding the modal µ alternation hierarchy is exactly equivalent to deciding the Rabin-Mostowski index of alternating parity automata. The corresponding problem has also been studied for automata operating on words [3] and automata which are deterministic [13,12], or non-deterministic [4,7] rather than alternating. As will be highlighted throughout this paper, many of the methods used here are similar to methods applied to different types of automata.…”
Section: Related Workmentioning
confidence: 99%
“…As the characterization effectively yields an equivalent game automaton, we obtain procedures computing the alternating, weak alternating, and non-deterministic index for a given alternating automaton equivalent to some game automaton. This paper collects results from two conference papers: [Facchini et al 2013] and [Facchini et al 2015]. Additionally, it contains a discussion of the maximality of the class of game automata, which adapts a reasoning from [Duparc et al 2011] to the index problem.…”
Section: Introductionmentioning
confidence: 99%